Identitas Negara-Bangsa dan Kebangkitan Islam:Perbandingan Malaysia dan Indonesia - Mujani, Saiful (Studia Islamika, 1994)
Started writing, Nash describes an event that took the surrender of the armed struggle of fifteen years by claiming around 40,000 people, the struggle pursued by the Darul Islam (DI)-metaphor-led Islamic state Kartosuwiryo (1905-1962). DI is based on the struggle of Islam and not much is known of the international community was taking place long before the concept of "Islamic fundamentalism" known among journalists or academicsDOI: 10.15408/sdi.v1i2.862